1978
DOI: 10.1159/000241138
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α-Fetoprotein, Albumin and Total Serum Protein in Neonatal Pigs

Abstract: Studies on the incorporation of 3H-leucine established that synthesis of α-fetoprotein (AFP) does occur in the neonatal pig. This synthesis probably accounts for the increase in AFP concentration from 0.46 mg/ml on the day after birth to the maximum value of 1.02 mg/ml found 5 days after birth. After the 5th day, the concentration decreases successively and AFP cannot be detected by electroimmunoassay in the sera of 8-week-old pigs. During the first 3 weeks of extrauterine life, the albumin concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 13 publications
6
22
0
Order By: Relevance
“…Some of our results confirm those of previous authors over a more restricted range of gesta tion on total protein, albumin and AFP in fe tal pig serum [10,22,24,36], Transferrin and fetuin do not appear to have been estimated previously in fetal pig plasma nor are there any quantitative studies available of proteins in fetal pig CSF.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Some of our results confirm those of previous authors over a more restricted range of gesta tion on total protein, albumin and AFP in fe tal pig serum [10,22,24,36], Transferrin and fetuin do not appear to have been estimated previously in fetal pig plasma nor are there any quantitative studies available of proteins in fetal pig CSF.…”
Section: Discussionsupporting
confidence: 92%
“…These authors found a value of only 100±56 mg/100 ml for serum transferrin in newborn piglets, which subsequently rose to adult lev els by 3 weeks postnatal. It is not clear if there is a gradual decline from approximately 500 mg/100 ml at 109 days (table II) to a newborn value of less than 200 mg/100 ml [37], There may be a sudden drop at the time of birth as is the case for AFP [22]. In contrast, there is a very marked rise in serum albumin concen tration in the newborn and postnatal period in the pig [22].…”
Section: Proteins In Fetal Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma proteins in the developing pig have been studied extensively by Ingvarsson, Carlsson & Karlsson (1978), who described an increased synthesis of albumin in the new-born pig. Stone (1981) found that during fetal growth a-fetoprotein declined as albumin increased.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Carlsson et al (7), Ingvarsson et al (13) have observed that neonatal piglets produce a relatively high amount of afetoprotein. This fact suggested that some physiological condition of suckling piglets seems to be at a fetal stage.…”
mentioning
confidence: 99%